Pengaruh Emotional Demontrion (Emo Demo) Terhadap Pengetahuan Dan Sikap Ibu Bayi 6-24 Bulan Tentang Pemberian Makanan Pendamping Air Susu Ibu Di Puskemas Dolo Kabupaten Sigi - Susanti, Tabah; Masud, Farida (-, 2025)
This study examines the influence of emotional demonstrations (Emo Demo) on the knowledge and attitudes of mothers of 6-24-month-old infants regarding complementary feeding (MPASI) at the Dolo Community Health Center in Sigi Regency. The knowledge of mothers of 6-24-month-old infants was assessed before and after counseling using the Emo Demo method. This research used a quantitative experimental approach using a quasi-experimental approach. The research design used in this study was a One Group Pretest Posttest Design, which provides an initial test (pretest) before treatment is given, and then a posttest is given after treatment. The results showed that of the 30 sampled individuals, before being given emotional demonstrations regarding complementary feeding, the average score was 55.10 (poor knowledge) with a standard deviation of 5.35 and a standard mean error of 0.977. Meanwhile, after receiving an emotional demonstration regarding complementary foods, the average score was 78.70 (good knowledge) with a standard deviation of 4.41 and a standard mean error of 0.805. This indicates a change in knowledge before and after the emotional demonstration.